Sequence variant at 4q25 near PITX2 associates with appendicitis - Ragnar P. Kristjansson (Nature Portfolio, 2017)
Abstract Appendicitis is one of the most common conditions requiring acute surgery and can pose a threat to the lives of affected individuals. We performed a genome-wide association study of appendicitis in 7,276 Icelandic and 1,139 Dutch cases and large groups of controls. In a combined analysis of the Icelandic and Dutch data, we detected a single signal represented by an intergenic variant rs2129979 [G] close to the gene PITX2 associating with increased risk of appendicitis (OR = 1.15, P = 1.8 × 10−11). We only observe the association in patients diagnosed in adulthood. The marker is close to, but distinct from, a set of markers reported to associate with atrial fibrillation, which have been linked to PITX2. PITX2 has been implicated in determination of right-left symmetry during development. Anomalies in organ arrangement have been linked to increased prevalence of gastrointestinal and intra-abdominal complications, which may explain the effect of rs2129979 on appendicitis risk.